2014
DOI: 10.1007/s10212-014-0219-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing elementary and secondary school students’ ability to perform historical perspective taking: the constructing of valid and reliable measure instruments

Abstract: Historical reasoning competencies play an important role in history education. However, valid and reliable large-scale measurement instruments to assess these competencies are scarce. This study considers two instruments for measuring students' ability to perform historical perspective taking (HPT) as a historical reasoning competency. The instruments have been tested for validity and reliability among 1,270 Dutch upper elementary and secondary school students, ranging in age from 10 to 17 years. One instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
1
36
0
2
Order By: Relevance
“…Moreover, we focused on pre-university students aged 15-16 because, based on previous research (e.g., Berti et al, 2009;Hartmann & Hasselhorn, 2008;Huijgen et al, 2014), we concluded that students are able to perform HPT at this age, thus enabling us to investigate the reasoning that underlies one's ability to take a historical perspective.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, we focused on pre-university students aged 15-16 because, based on previous research (e.g., Berti et al, 2009;Hartmann & Hasselhorn, 2008;Huijgen et al, 2014), we concluded that students are able to perform HPT at this age, thus enabling us to investigate the reasoning that underlies one's ability to take a historical perspective.…”
Section: Methodsmentioning
confidence: 99%
“…They found that approximately 90% of the participants in the study successfully performed HPT. Huijgen et al (2014) used the same instrument to test the ability of 1,270 elementary and secondary students aged between 10-17 years to perform HPT. Their results showed that even upper elementary school students are capable of performing some elements of HPT, though older students performed HPT more successfully than younger students.…”
Section: Students' Ability To Perform Hptmentioning
confidence: 99%
See 3 more Smart Citations